Peran Lingkungan Sekolah dalam Membentuk Kebiasaan Membaca Siswa Pada Pembelajaran SKI di Madrasah Aliyah Sunan Ampel Krejengan - Jauharatul Kamalia; Edi Kurniawan Farid; Mohamad Solihin (Irfani, 2026)
Reading habits are an important aspect in improving the quality of learning and intellectual development of students. The school environment has a strategic role in forming and fostering reading habits, especially through supporting facilities, literacy culture, as well as the role of educators and education staff. This research aims to describe the role of the school environment in forming students’ reading habits at Madrasah Aliyah Sunan Ampel Kamalkuning Krejengan Probolinggo. This research uses a qualitative approach with descriptive research type. Data collection techniques are carried out through observation, interviews and documentation. Research subjects included madrasa heads, teachers, and students. The research results show that the school environment plays a role in forming students’ reading habits through the provision of literacy facilities such as libraries and reading corners, familiarization with reading activities before learning, teacher example, and madrasah literacy programs. Supporting factors in forming reading habits include the availability of facilities, teacher support, and madrasah policies, while inhibiting factors include limited book collections, students’ varying reading interests, and the influence of the use of gadgets. Thus, it can be concluded that the school environment has a significant role in forming students’ reading habits, although efforts are still needed to strengthen literacy programs so that reading habits can develop optimally